Analysis of the metallic structure of microspheres produced by printing of aluminum alloys from the liquid melt. (7th December 2018) - Gerdes, Björn; Breitwieser, Matthias; Kaltenbach, Thomas; Jehle, Michael; Wilde, Jürgen; Zengerle, Roland; Koltay, Peter; Riegger, Lutz
Abstract: This work presents an analysis of the metallic structure of microspheres produced by drop-on-demand printing of the aluminum alloy AlSi12 directly printed from the liquid melt via StarJet technology. AlSi alloys are commonly used in casting processes, but microdroplets from these materials could potentially be used for additive manufacturing of metal and composite parts. Recently, several printing technologies were presented that enable the drop-on-demand printing of Al-alloy microdroplets. However, the material distribution and metallic structure inside of printed droplets is expected to be significantly different from the bulk material properties, and hardly any data on the microscopic structure of small droplets that have undergone rapid solidification has been published so far. Therefore, a microscopic in-depth study of microdroplets printed directly from the metal melt has been carried out: By the means of energy-dispersive x-ray spectroscopy (EDX), scanning electron microscopy (SEM), Auger electron spectroscopy (AES) and optical microscopy the material properties as well as the droplet morphology are investigated for the first time. The analysis demonstrates that the Al alloy droplets printed via StarJet technology exhibit almost no oxidation during the printing process and can therefore potentially be used for additive manufacturing of metal parts. Moreover, the metallurgical structure inside the droplets is analyzed. It exhibits significant difference to the bulk material in terms of the average secondary dendrite arm spacing.